Work Ethic, Amanah, and Integrity in the Qur’an: Constructing an Integrative Ethical Framework - Nazilatul Fatihah Firdaus; Husein Aziz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Contemporary professional life increasingly demands strong ethical foundations to address problems such as declining work ethics, weak accountability, and the erosion of integrity in various social and institutional contexts. Within Islamic intellectual tradition, the Qur’an offers a comprehensive moral framework that emphasizes ethical responsibility in human conduct. However, previous studies often examine the values of work ethic, amanah (trustworthiness), and integrity separately, resulting in a fragmented understanding of their interrelated ethical structure. This study aims to analyze the Qur’anic construction of work ethic, amanah, and integrity as an integrated ethical framework and to explore their relevance for strengthening moral character and professional culture in contemporary society. This research employs qualitative library research using thematic analysis of Qur’anic verses supported by classical and contemporary exegetical literature. The findings demonstrate that the Qur’an conceptualizes work ethic as diligence and responsibility in fulfilling human duties, amanah as moral accountability in carrying entrusted responsibilities, and integrity as consistency between faith, speech, and action. These values are not independent but form an interconnected ethical system that guides individuals toward responsible and ethical conduct. The study concludes that the Qur’anic framework of work ethic, amanah, and integrity provides a significant moral foundation for reinforcing professionalism, accountability, and ethical work culture in the modern era.